Optimising laser stereolithography for constructing electronic packages onto novel substrates - Plant, Robert J. (2024)
Additive manufacturing (AM) has matured from its initial concept as a prototyping technique to an established industrial manufacturing process for which compliance with relevant standards is required. Here, we investigate inserting components into geometries constructed directly onto non-standard substrates using stereolithography (SLA), for the purpose of electronics packaging. Silicon nitride is of particular interest as the interfacial material when packaging semiconductors and technologies such as silicon interconnect fabric. Compared to conventional encapsulation processes, SLA avoids elevated temperatures and stresses while permitting much greater flexibility to arrange components in three dimensions. This can enable an increased feature density, optimised packages for confined spaces, functional packaging to complement the operation of the device, and enables rapid production for bespoke applications.